2010
DOI: 10.1002/dc.21457
|View full text |Cite
|
Sign up to set email alerts
|

Cellient™ automated cell block versus traditional cell block preparation: A comparison of morphologic features and immunohistochemical staining

Abstract: Traditional cell block (TCB) sections serve as an important diagnostic adjunct to cytologic smears but are also used today as a reliable preparation for immunohistochemical (IHC) studies. There are many ways to prepare a cell block and the methods continue to be revised. In this study, we compare the TCB with the Cellient TM automated cell block system. Thirty-five cell blocks were obtained from 16 benign and 19 malignant nongynecologic cytology specimens at a large university teaching hospital and prepared ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
75
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 59 publications
7
75
3
Order By: Relevance
“…Another option for making a CB is Cellient (Hologic Inc, Marlborough, Mass), a relatively new proprietary instrument that makes a CB from needle rinses in Cytolyt, an alcoholbased fixative, by first vortexing the sample and then removing an aliquot of the sample for a ThinPrep (Hologic Inc) slide and an aliquot to form a paraffin-embedded cell block. 3 Because this technique uses just an aliquot of the sample to produce a CB, it does not capture all the material in the FNAB. In addition, we sought to avoid using alcohol-based fixatives such as Cytolyt, which can potentially alter IHC staining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another option for making a CB is Cellient (Hologic Inc, Marlborough, Mass), a relatively new proprietary instrument that makes a CB from needle rinses in Cytolyt, an alcoholbased fixative, by first vortexing the sample and then removing an aliquot of the sample for a ThinPrep (Hologic Inc) slide and an aliquot to form a paraffin-embedded cell block. 3 Because this technique uses just an aliquot of the sample to produce a CB, it does not capture all the material in the FNAB. In addition, we sought to avoid using alcohol-based fixatives such as Cytolyt, which can potentially alter IHC staining.…”
Section: Introductionmentioning
confidence: 99%
“…Routine hematoxylin and eosin (H & E)-stained sections of a high-quality CB can provide both cytologic and architectural detail to support the cytomorphologic findings on direct smears. [1][2][3] A good CB can be very useful for immunohistochemical (IHC) staining as well as cytochemical staining and molecular diagnostic studies such as fluorescence in situ hybridization, polymerase chain reaction, and next-generation sequencing. 4 To the best of our knowledge, there currently is no standardized method for producing a CB from an FNAB.…”
Section: Introductionmentioning
confidence: 99%
“…However the newer techniques utilize methanol-based fixation, which interfere with immunohistochemical analysis especially for ER, PR, MIB 1 and Her 2 neu [9][10][11]. However this issue may be overcome by formalin pre-fixation prior to Cellient [7].…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemistry is increasingly used as an adjunct to conventional cytomorphology in the diagnosis of fine needle aspirates. But some limitations like, limited number of smears for testing, not necessarily specific staining and lack of parallel samples of the same cells for additional or control tests occurs with smears [4]. Moreover, use of considerable volume of antibodies to cover large areas of less cellular smears increases the cost [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the examination of cytologic material for evidence of malignant neoplasm by the cell block technique is an eminently worthwhile and dependable procedure provided suitable methods and proper diagnostic criteria are provided [2,3]. The improved availability of Immuno Histochemical (IHC) stains in recent years has also increased the desire for cell block preparation in cytopathology laboratories because, larger numbers of initial diagnoses of today are being evaluated by fine needle aspiration versus the past, when a biopsy or resection was available to the pathologist [4]. Contrary to the attempt to single out smear or cell block as being superior to the other, the main aim of this study was to access the utility of cell block in increasing the cytodiagnosis of fine needle aspirates and fluids and to apply immuno histochemical markers on cell blocks and evaluate whether the cell block material fixed in 10% formalin, is suitable for immunohistochemistry (IHC).…”
Section: Introductionmentioning
confidence: 99%